Nutrition labelling and the choices logo in Israel: positions and perceptions of leading health policy makers. Issue 1 (9th May 2013) - Gesser‐Edelsburg, A.; Endevelt, R.; Tirosh‐Kamienchick, Y.
Abstract Background Based on the Social Marketing approach and Diffusion of Innovations Theory that indicates the importance of opinion leaders with respect to the spreading of new ideas, concepts or practices within a community, the present study aimed to examine positions and perceptions of Israeli leading dietitians and health officials regarding nutrition labelling and the Choices logo, before it was launched in Israel in February 2011, as well as how they would communicate it to the public as agents of influence. Methods The study involved in‐depth face‐to‐face and telephone interviews with 15 senior dietitians and Health Ministry officials using semi‐structured protocols including questions about nutrition labelling and the Choices logo. Results The respondents considered that the nutrition facts panels usually found on the backs of packages are too complicated for the average consumer. Simiularly, fronts of packages are cluttered with advertisements and health claims, causing confusion. The study participants would like to see an integrative label on the front of the package to facilitate consumers' decisions. However, the Choices logo raises ethical and social questions about the conflict between corporate interests and public health: (i) the label's relativity versus objectivity; (ii) the consumer's responsibility to create a balanced diet; (iii) the label's credibility; and (iv) bias against companies, products and audiences. Conclusions The results of the present study highlight the importance of a need for an integrated programme of nutrition promotion, including the use of social marketing based on a cooperative effort between the food industry, regulators and professionals, to recommend changes and adjustments in nutritional front of package labelling with the aim of promoting healthier nutrition consumption.